A Castle Surrounded by Hungry Wolves: Toward a Stage Theory of the Uses of the Future. (March 2020) - Inayatullah, Sohail
Drawing on hundreds of case studies and decades of using the future in professional settings, this article moves toward a stage theory—to begin with, a conceptual framework—to using the future. This extends the Six Pillars framework and accompanying tools (scenarios, causal layered analysis, visioning) by inquiring which methods and tools are appropriate for which national, institutional, organizational, and personal contexts. Seven stages (nonlinear, spiral) are suggested. The first is perceived injustice—"it is not fair." The second is risk mitigation. The third is creating alternative futures. The fourth is directionality, the vision. The fifth is "making the vision real." The sixth is metaphor. The final state is personal and focused on using the mantra technique to transform the narrative. This approach intends to assist change agents in understanding the worldview context they are working—co-creating—with.